Distinct transcriptional profiles of Leptospira borgpetersenii serovar Hardjo strains JB197 and HB203 cultured at different temperatures. - Ellie J Putz; Sathesh K Sivasankaran; Luis G V Fernandes; Brian Brunelle; John D Lippolis; David P Alt; Darrell O Bayles; Richard L Hornsby; Jarlath E Nally (Public Library of Science (PLoS), 2021)
Background Leptospirosis is a zoonotic, bacterial disease, posing significant health risks to humans, livestock, and companion animals around the world. Symptoms range from asymptomatic to multi-organ failure in severe cases. Complex species-specific interactions exist between animal hosts and the infecting species, serovar, and strain of pathogen. Leptospira borgpetersenii serovar Hardjo strains HB203 and JB197 have a high level of genetic homology but cause different clinical presentation in the hamster model of infection; HB203 colonizes the kidney and presents with chronic shedding while JB197 causes severe organ failure and mortality. This study examines the transcriptome of L. borgpetersenii and characterizes differential gene expression profiles of strains HB203 and JB197 cultured at temperatures during routine laboratory conditions (29°C) and encountered during host infection (37°C). Methodology/principal findings L. borgpetersenii serovar Hardjo strains JB197 and HB203 were isolated from the kidneys of experimentally infected hamsters and maintained at 29°C and 37°C. RNAseq revealed distinct gene expression profiles; 440 genes were differentially expressed (DE) between JB197 and HB203 at 29°C, and 179 genes were DE between strains at 37°C. Comparison of JB197 cultured at 29°C and 37°C identified 135 DE genes while 41 genes were DE in HB203 with those same culture conditions. The consistent differential expression of ligB, which encodes the outer membrane virulence factor LigB, was validated by immunoblotting and 2D-DIGE. Differential expression of lipopolysaccharide was also observed between JB197 and HB203. Conclusions/significance Investigation of the L. borgpetersenii JB197 and HB203 transcriptome provides unique insight into the mechanistic differences between acute and chronic disease. Characterizing the nuances of strain to strain differences and investigating the environmental sensitivity of Leptospira to temperature is critical to the development and progress of leptospirosis prevention and treatment technologies, and is an important consideration when serovars are selected and propagated for use as bacterin vaccines as well as for the identification of novel therapeutic targets.